Democracy and civil society in the 70's: an analysis made by academic marxists - Silva, Luiz Fernando da (Universidade Estadual Paulista / UNESP, 2009)
This paper discusses the development of the concepts of democracy and civil society in Brazil in the 70's. ft status that the first ideas about them were strongly influenced by the academic staff of a marxist live. It also points out that these concepts could be developed due to the idea of structural dependence and the conception of a burocratic and authoritarian state.